Pengaruh Net Profit Margin Return On Asset Dan Return On Equity Terhadap Harga Saham - Anugrah Harika Putra; Nanu Hasanuh (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of Net Proft Margin, Return On Assets, and Return On Equity Against the Stock Price of Companies in the Financial Services Subsector Listed on the Indonesia Stock Exchange in 2015-2018. This research has occurred a phenomenon and identification of a problem that is quite interesting. The data source used from this research is only secondary data. The selection of samples is based on the criteria and subsector companies of 17 financial institutions and samples taken by 8 companies using the purposive sampling method in the financial institutions subsector companies. This study uses the data analysis methods of classical assumptions and hypothesis testing. The results showed that partially Net Profit Margin and Return On Assets have a significant effect on Stock Prices and partially showed Return On Equity had no significant effect on Stock Prices. Simultaneously, Net Profit Margin, Return On Asset, and Return On Equity have a significant effect on stock price. Keywords : NPM, ROA, ROE, Stock Price